Simulation-Based Study of Self-Excited SRG by Using Nonlinear ‎Models and Open-Loop Excitation Strategies - Balasubramanian, V.; Radhika, S.; Nayagam , V. Senthil (International Journal of Basic and Applied Sciences, 2025)
This research offers a comprehensive examination of the operational principles and dynamic characteristics of the Switched Reluctance Gen‎erator (SRG) when functioning in self-excited mode. The focus is on the rotor’s inherent inclination to align with the path of least reluctance, ‎requiring the separate activation of each phase via appropriate power electronic converters and control systems. Recent studies emphasize ‎the increasing importance of the SRG in renewable energy and automotive industries. The study highlights the shortcomings of linear mod‎eling for precise simulation, especially when neglecting magnetic saturation and nonlinearities in the machine. A nonlinear model that in‎cludes magnetic saturation and utilizes a Fourier series-based inductance profile was developed in MATLAB/Simulink using data from an ‎existing prototype. The excitation approach used a parallel capacitor alongside a half-bridge converter, and simulations were performed in ‎open-loop mode. The research examined differences in speed, actuation angles, and load conditions, uncovering their effects on both transi‎ent and steady-state voltage performance. Results indicate that angle modulation greatly influences ignition timing and overall system effi‎ciency. This study enhances the basic comprehension of SRG functioning under self-excited conditions and aids future uses in energy-efficient systems.